2022
DOI: 10.3390/ijerph191912217
|View full text |Cite
|
Sign up to set email alerts
|

PTSD and Depression Symptoms Increase Women’s Risk for Experiencing Future Intimate Partner Violence

Abstract: Psychological distress may impact women’s risk for future intimate partner violence (IPV). Yet, limited research has utilized longitudinal research designs and there is a scarcity of research looking at the three most commonly implicated mental health factors—posttraumatic stress disorder (PTSD), depression, and alcohol use—within the same study. Research is especially scarce for women veterans, who experience substantial risk for these mental health concerns and experiencing IPV. This study examined the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
2
0
1
Order By: Relevance
“…Research has additionally shown associations between the current or daily severity of various PTSD symptom clusters (e.g., hyperarousal, avoidance) and daily risks of substance use (Sullivan et al, 2016(Sullivan et al, , 2020. Further, as noted, prior research has shown associations between PTSS and a risk of incident IPV among IPV survivors, thus generating additional risks (Iverson et al, 2013(Iverson et al, , 2022. To sufficiently support women in substance use treatment, the findings from this study suggest that it is imperative that treatment settings simultaneously address IPV and trauma during goal-setting and linkage to care.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Research has additionally shown associations between the current or daily severity of various PTSD symptom clusters (e.g., hyperarousal, avoidance) and daily risks of substance use (Sullivan et al, 2016(Sullivan et al, , 2020. Further, as noted, prior research has shown associations between PTSS and a risk of incident IPV among IPV survivors, thus generating additional risks (Iverson et al, 2013(Iverson et al, , 2022. To sufficiently support women in substance use treatment, the findings from this study suggest that it is imperative that treatment settings simultaneously address IPV and trauma during goal-setting and linkage to care.…”
Section: Discussionmentioning
confidence: 86%
“…For example, in a sample of U.S. college students, Sabina and Straus (2008) found that exposure to multiple forms of IPV was the strongest predictor of experiencing PTSS. Additionally, research has shown that PTSS among IPV survivors may also increase the risk of future IPV (Iverson et al., 2013, 2022). This is critical as women who use and misuse substances already face an increased risk for a range of adverse outcomes, such as poor mental health and HIV, and IPV may further exacerbate these risks (El‐Bassel et al., 2022; National Institute on Drug Abuse, 2020; U.N. Programme on HIV/AIDS, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Violência doméstica e saúde mental Transtornos depressivos são a principal condição psiquiátrica encontrada em vítimas de VD, com prevalências que variam entre 38% e 83%, a depender da amostra estudada [24]. Quanto mais graves os abusos sofridos, maior também é a chance de desenvolver Transtorno de Estresse Pós-traumático (TEPT), cujos sintomas podem perdurar durante anos, mesmo após o fim do relacionamento, e também aumentam o risco de recorrência de violências [25]. Ansiedade, dor crônica, transtornos por uso de substâncias e ideação suicida também são mais prevalentes em vítimas de VPI em relação à população geral [18,20,26].…”
Section: Resultsunclassified
“…Although causality cannot be definitively established, these findings suggest a bidirectional relationship between exposure to IPV and probable depression in both the prenatal and postnatal periods. While the mental health effects of IPV victimization during the perinatal period may stem from the combined impact of stress, hormonal changes, and lack of support in (expectant) women [ 23 ], it is theoretically plausible that e.g., depression symptoms may increase the risk of IPV victimization through a reduced cognitive and affective capacity by which to recognize threat [ 24 , 25 ], thereby complicating decision-making and responses to danger cues.…”
Section: Introductionmentioning
confidence: 99%